Efeito do turno de coleta sobre comunidades de formigas epigéicas (Hymenoptera: Formicidae) em áreas de Eucalyptus cloeziana e de cerrado - Tavares, Antônio A. (2008)
This study aimed at evaluating the effect of collect time (day and night) on ant fauna attracted to baits in areas of Eucalyptus cloeziana (Myrtaceae) and cerrado. The ants were collected in Fazenda Boa Vista, Mannesmann Fi - El Florestal Ltda, Paineiras, Minas Gerais State. Eigthteen sample units were collected: 12 in E. cloezina and six in cerrado. Each sample unit consisted of three plots (25 x 35 m each). The plot consisted of 34 baits distributed in a grid pattern at 5 m intervals. The sampling was carried out in the diurnal and nocturnal period. The results obtained revealed that both type of vegetation (cerrado x Eucalyptus) and the collect time (day x night) had a significative influence on the epigaeic ant fauna. The ordination (DCA) indicated that collect time effect was more important to fauna structuration than the vegetation effect. Brachymyrmex sp.1, Brachymyrmex sp.2, Camponotus crassus Mayr, Camponotus rufipes (Fabricius), Cephalotes pusillus (Klug) and Ectatomma brunneum Smith were indicator species of nocturnal period, and Camponotus renggeri-Emery, Camponotus atriceps (Smith), Camponotus melanoticus Emery and Paratrechina sp.1 were indicators of nocturnal period.